Vineyard landscapes in Italy: cases of territorial requalification and governance strategies. (2nd October 2016) - Camaioni, Chiara; D'Onofrio, Rosalba; Pierantoni, Ilenia; Sargolini, Massimo
Abstract: The success of a food product is also the success of the territory that produced it. Based on this idea, we address the connection between landscape and quality wine in order to promote new sustainable development of rural territories. We use regulatory plans for 'Wine Cities' of Bomporto, Pramaggiore and San Martino sulla Marrucina (Italy) to highlight the ability of new urban-planning instruments to deal with different aspects relating to quality food and agriculture. The goal of the plans is to improve and renew the rural territory. Based on the Wine City Guidelines, the local urban plans for these towns provide useful indications, suggestions and rules for territorial improvement and transformation by way of enhancing the rural landscape and quality wine production. In promoting this new type of development, these plans encourage the direct involvement of local communities and manufacturing companies in sharing and promoting common objectives and development strategies.